Open-loop and closed-loop control of posture: Stabilogram-diffusion analysis of center-of-pressure trajectories among people with stroke. (August 2020) - Treger, Iuli; Mizrachi, Nama; Melzer, Itshak
Highlights: People with stroke demonstrated significantly greater postural sway than healthy adults. People with stroke demonstrated larger distance of sway until closed-loop control took place. People with stroke have a significantly greater reliance on visual input compared with healthy subjects. Abstract: Many people with stroke (PwS) demonstrate reduced balance and increased postural sway afterwards, which may ultimately lead to falls and injury. In this study, we aimed to better understand postural sway behavior and the mechanisms of balance control by examining balance in upright standing among PwS using methods from statistical mechanics i.e., the Stabilogram diffusion analysis (SDA). Center-of-pressure displacements while standing still were measured in 25 PwS and 11 healthy subjects. The traditional postural sway parameters were measured, and the SDA was used to characterize balance control in eyes-open and eyes-closed conditions. We found that PwS demonstrated significantly greater postural sway in the mediolateral and anterior–posterior directions and significantly higher SDA short-term diffusion coefficients and critical displacement in both eyes-open and eyes-closed conditions. There was also a significant group-by-condition interaction, whereas PwS demonstrated more sway in the eyes-closed condition. The SDA analysis revealed unstable behavior during short-term intervals, interpreted as larger distance of sway until closed-loop control took place. This significant group-by-condition interaction suggests that PwS have a significantly greater reliance on visual input compared with healthy subjects.